(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper critically examines the judicial pronouncements on the law of insanity and their impact on the protection of the rights of persons with mental disabilities in India, with specific reference to the state of Gujarat. The paper explores key legal provisions, including Section 84 of the Indian Penal Code and the Mental Health Care Act, 2017, which provide legal frameworks for individuals with mental health conditions, both in criminal law and in protecting their civil rights. The paper delves into landmark judicial decisions, such as R v. McNaghten and several Supreme Court rulings, which have shaped the interpretation of the insanity defense in India. It also analyzes the evolving role of the judiciary in ensuring that persons with mental disabilities receive appropriate treatment and their legal rights are protected. The paper evaluates the practical implications of these judgments in Gujarat, examining how the state’s legal and healthcare systems respond to the needs of mentally disabled individuals. Finally, the paper highlights the gaps in the existing legal and healthcare systems and suggests reforms to strengthen the protection of these vulnerable individuals.